Weaving the Future of Islamic Civilization 2.0: Prospects and Challenges of a Mini-Research - Mustafa Kamil Thahir (Journal Of Social Science (JoSS), 2025)
This research discusses the concept of "Islamic Civilization 2.0," which aims to build a dynamic and relevant vision of Islamic civilization in the 21st century. In the context of global challenges such as social inequality, environmental degradation, and cultural polarization, it is important to integrate Islamic values with an inclusive and cosmopolitan approach. The purpose of this study is to develop a holistic framework that integrates Islamic epistemology, cosmopolitan values, and inclusive approaches, and to provide practical recommendations for policy makers, educators, and academics in applying those values to face contemporary challenges. This study uses a qualitative approach with a literature study design, analyzing the works of Husein Heriyanto, Bruce Lawrence, and Supriyanto Abdi. Data were collected from books, journal articles, and relevant documents, then analyzed using thematic analysis to develop a holistic framework. The research found that integrating Islamic epistemology, cosmopolitan values and inclusive approaches can form a comprehensive framework for the revitalization of Islamic thought and practice. This framework emphasizes the need for engagement in intercultural dialogue and the development of human values-based science inspired by Islam. This research provides guidance for policymakers, educators and academics to implement policies and curricula that are in line with maqasid al-syariah (the higher purpose of Islamic law). It concludes that "Islamic Civilization 2.0" offers a balanced approach to contemporary challenges by integrating Islamic values in a global context.